Emerging tools for studying single entity electrochemistry. (10th October 2016) - Wang, Yixian; Shan, Xiaonan; Tao, Nongjian
Abstract : Electrochemistry studies charge transfer and related processes at various microscopic structures (atomic steps, islands, pits and kinks on electrodes), and mesoscopic materials (nanoparticles, nanowires, viruses, vesicles and cells) made by nature and humans, involving ions and molecules. The traditional approach measures averaged electrochemical quantities of a large ensemble of these individual entities, including the microstructures, mesoscopic materials, ions and molecules. There is a need to develop tools to study single entities because a real system is usually heterogeneous, e.g., containing nanoparticles with different sizes and shapes. Even in the case of "homogeneous" molecules, they bind to different microscopic structures of an electrode, assume different conformations and fluctuate over time, leading to heterogeneous reactions. Here we highlight some emerging tools for studying single entity electrochemistry, discuss their strengths and weaknesses, and provide personal views on the need for tools with new capabilities for further advancing single entity electrochemistry.